Metabolic, pathological, and genetic analyses of foals neonatal foals that died in Noma horses - ZHANG, Chunhua; UNE, Yumi; ONO, Tetsushi; KUTARA, Kenji; HIASA, Yasuharu; OHZAWA, Emi; LE, Nu Anh Thu; KUNIEDA, Tetsuo; KITAGAWA, Hitoshi; IWATA, Eri; KADEKARU, Sho; HISAEDA, Keiichi; et al. (Journal of Equine Science, 2025)
We evaluated metabolic abnormalities in six neonatal Noma foals (Nos. 54–57, 62, and 66) that died shortly after birth, using laboratory tests, pathological examinations, serum amino acid (AA) analyses, gas chromatography/mass spectrometry (GC/MS), and genetic analyses. Nonspecific clinical symptoms, such as poor suckling and weakness, were commonly observed at birth. Sepsis caused by various bacterial infections was detected in foal Nos. 54, 62, and 66, while a heart malformation was identified in foal No. 57. Laboratory tests showed high aspartate transaminase, lactate dehydrogenase, and creatine kinase levels and low globulin and glucose levels in dead foals. The AA and GC/MS analyses revealed elevated levels of ammonia, orotic acid, and uracil in foal Nos. 54 and 55, while citrulline, arginine, and ornithine levels were low or within normal ranges, suggesting accelerated pyrimidine synthesis and suppressed urea cycle activity. Foal No. 56 had high uric acid and tyrosine levels, hypoglycemia, and liver dysfunction, suggesting glycogen storage disease. In foal No. 57, hypertyrosinemia was suggested because of high phenylalanine and tyrosine levels. We conducted a sequencing analysis of the ornithine transcarbamylase, argininosuccinatelyase, argininosuccinate synthase 1, uridine monophosphate synthase, G6PC1, and G6PT1/SLC37A4 genes associated with metabolic disorders. However, no mutations were detected. In conclusion, although metabolic pathways abnormalities resembling certain hereditary metabolic disorders were observed in neonatal foals that died in Noma horses, no specific mutations were identified in candidate genes, making hereditary disorders less likely.